Investigation of Information and Communication Technologies (ICT) Usage in the Business Relations of the Agri-Food Econ - Boros-Papp, Sándor; Várallyai, László (International Journal of Engineering and Management Sciences, 2018)
Small and medium-sized enterprises are the engines of Europe's economy. This is demonstrated by the European Small Enterprises Charta, adopted in 2000, and by the fact that this sector employs more than 90 million people. Appropriate information and communication technology is essential to maintain their ability to function effectively and competitively. They need to know how to use these technologies for their smoot growth in productivity. The purpose of our study is to assess the regional ICT penetration of the Hungarian SME sector and compare this to that of the EU Member States.